2021
DOI: 10.1002/brb3.2370
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting Pakistani young adults’ intentions to uptake COVID‐19 vaccination: An extension of the theory of planned behavior

Abstract: Introduction: Aside from personal beliefs, young adults' intention to uptake the COVID-19 vaccine can be influenced by their fear of COVID-19 and perceived infectability of COVID-19. The present study incorporated fear of COVID-19 and perceived infectability with the theory of planned behavior (TPB) to form an expanded TPB to analyze factors affecting Pakistani young adults' intentions to uptake the COVID-vaccine in Pakistan. Methods: A cross-sectional study was conducted and recruited participants from Pakist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 33 publications
2
22
1
Order By: Relevance
“…Behaviour control perception results in this research are also different from those indicated by Ullah et al (22) and Yahaghi et al (21) Which showed the influence of behavior control perception on the intention or willingness to be vaccinated, whereas this study showed different results. (21,22) Research results related to sex type on COVID-19 vaccination are also not similar to the ones presented by Ishimaru et al (23) Which revealed a significant relationship between sex and willingness to receive COVID-19 vaccination which is not shown in this research. (23) Research result based on the age dimension is also different from the ones produced by Lazarus et al (24) Which concluded that Age could be a determining factor in enhancing COVID-19 vaccination involvement which is not found in this research.…”
Section: Discussioncontrasting
confidence: 99%
“…Behaviour control perception results in this research are also different from those indicated by Ullah et al (22) and Yahaghi et al (21) Which showed the influence of behavior control perception on the intention or willingness to be vaccinated, whereas this study showed different results. (21,22) Research results related to sex type on COVID-19 vaccination are also not similar to the ones presented by Ishimaru et al (23) Which revealed a significant relationship between sex and willingness to receive COVID-19 vaccination which is not shown in this research. (23) Research result based on the age dimension is also different from the ones produced by Lazarus et al (24) Which concluded that Age could be a determining factor in enhancing COVID-19 vaccination involvement which is not found in this research.…”
Section: Discussioncontrasting
confidence: 99%
“…Trust could be a solution for vaccine acceptance improvement [67], and this echoes the present study finding that opposing the government party is a factor for vaccine refusal. Some important behavior theories (e.g., protection motivation theory and theory of planned behavior) are relevant to vaccine hesitancy and discussed in the literature [68][69][70]; however, none of these was investigated in the present study. The present study used a single-item question to assess the participants' COVID-19 vaccine acceptance.…”
Section: Plos Onementioning
confidence: 99%
“…Other studies used psychological to understand the psychological correlates of vaccination intent. The theory of planned behavior explained how vaccination intent is associated with fear, perceived infectability, attitude, knowledge, risk perception and previous influenza vaccination [ 10 12 ]. Furthermore, the protection motivation theory explained how perceived severity shaped the motivation for vaccination against Covid-19 [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%